VECM Modeling of the Determinants of Decarbonization in Tunisia: The Role of Innovation and Renewable Energies - Amiri, Kaouther; Arfaoui, Lamia; Mannai, Sonia; Khouaja, Sihem Nasr (International Journal of Energy Economics and Policy, 2026)
This study analyzes the dynamic relationships between per capita CO2 emissions, renewable energy consumption, environmental innovation, and trade openness using a Vector Error Correction Model (VECM) over the period 1995–2024. The econometric analysis confirms the existence of a long-run cointegration relationship between these variables, highlighting a stable equilibrium mechanism linking environmental outcomes, technological progress, energy transition, and economic openness. Short-term causality tests reveal asymmetric interactions: environmental innovation is significantly influenced by shocks to renewable energy consumption and trade openness, while CO2 emissions show relative rigidity in the short run. Stability tests confirm the robustness of the model, and variance decomposition highlights the increasing influence of renewable energy on emissions, reflecting the gradual impact of energy transition policies. Environmental innovation emerges as a key driver influencing both renewable energy development and emissions dynamics, highlighting the crucial role of technological progress in achieving sustainability goals. Trade openness exerts an indirect but significant effect, interacting with innovation and energy over longer time horizons.